Overcoming cop culture? Organizational justice and police officers' attitudes toward the public - Myhill, A; Bradford, B (2013)
Purpose: The purpose of this paper is to test theories of organizational justice in the context of a police agency. Design/methodology/approach: Structural Equation Modelling (SEM) was used to analyze data from a survey of officers in a police force in England. Findings: The SEM showed that organizational justice was associated with positive attitudes towards serving members of the public. This relationship was mediated by commitment to elements of community policing and, for community police officers, by general satisfaction with the organization. Practical implications: The findings suggest that police managers committed to implementing process-based policing policies may need to ensure their organizations also implement internal policies and practices that are procedurally fair. Originality/value: This study is one of the first to apply the well established literature on organizational justice to the context of policing, and the first to examine the impact of organizational justice on alignment with community policing and the service model. © Emerald Group Publishing Limited.